Use of concrete formulations based on dredging sand in the fabrication of tetrapods for protection of harbour dykes - Hassoune Mehdi (EDP Sciences, 2021)
Port structures (quays and dykes) need an enormous consumption of materials, in particular concrete and its components, as well as sand, hence the need to develop alternative solutions using port dredging sand, estimated at thousands of tonnes through its use in the concrete that forms the blocks of the quay walls. After having demonstrated in a previous work the possibility of using the dredged sand from the port of Agadir in concrete formulations, the present work consists in showing the possibility of using the dredged sand from the port of Agadir in concrete formulations that can be used in the construction of concrete tetrapods from a concrete formulation based on dredged sand, more precisely 50% of the sand entering in the formulation is dredged sand extracted from the port of Agadir. The eventual use of dredged sand in the concrete of the tetrapods will lead to enormous gains in the quantities of sand and thus to a lower consumption of construction materials, and will also play a more important role in the preservation of the marine environment by avoiding the trapping of the dredged materials.